Motivation and challenges of Trainee Translators Participating in Translation Training - Jabu, Baso; Abduh, Amirullah; Rosmaladewi, Rosmaladewi (International Journal of Language Education, 2021)
The research on translation has been found very little particularly within the Indonesian context. This study aims to explore the motivation of students participating in translation training. This case study with an action learning model recruits 40 student participants. They involve in the research voluntarily and provide very insightful reflection at the end of the training session. The key to the findings is that students portray their future selves as the key motivational factor in participating in translation course. In addition, students face both linguistics and non-linguistics challenges in doing translation work. The finding has further implications for educators and translators and becomes a model for future translator training.